Pragmatic Functions of Questions in the Movie “A Man Called Otto” - Yaman, Nurinsani (Deskripsi Bahasa, 2026)
Questions serve a range of functions that go far beyond just seeking or requesting information. These different functions of questions depend on the context of the conversation. This study attempts to examine the various pragmatic functions of questions in the movie A Man Called Otto. The data were all the interrogative sentences in the movie. The data were analyzed using the framework proposed by Fareh and Moussa (2008), which identifies 35 distinct pragmatic functions of interrogative sentences. The findings of this study indicate that a total of 241 questions were identified, which consist of 132 (55%) yes/no questions and 109 (45%) WH questions. These questions were used to serve 21 pragmatic functions. Seeking/requesting information and seeking confirmation are the most frequent functions, making up 22.8% and 17.4% of the whole data, respectively. The analysis further shows that the identification of functions relies heavily on the context in which they are used. These findings contribute to linguistics studies by highlighting the diverse functions of questions. Pedagogically speaking, these findings should be taken into account by educators to enhance language learners’ communicative competence.